Bone Marrow Diffusion Measures Correlate with Dementia Severity in HIV Patients - Ragin, A.B.; Wu, Y.; Storey, P.; Cohen, B.A.; Edelman, R.R.; Epstein, L.G.; Gartner, S. (American Journal of Neuroradiology, 2006)
BACKGROUND AND PURPOSE: Escalation in monocyte trafficking from the bone marrow into the brain may play a critical role in central nervous system injury and cognitive deterioration in patients with HIV infection. This study tested the hypothesis that the mean diffusivity is sensitive to marrow changes in HIV patients and that these quantitative imaging measurements correlate with the severity of dementia.METHODS: The mean diffusivity (MD), determined for clival and calvarial marrow regions, was compared in 11 HIV-infected patients and 9 control subjects. The imaging measurements were also evaluated for relationships with dementia severity and markers of disease progression (CD4 and viral load in plasma).RESULTS: The MD was significantly reduced in both clival and calvarial marrow in HIV-infected patients (P =.006). Diffusion measurements for clival (P =.02) and for calvarial (P =.03) regions were significantly correlated with the severity of dementia.CONCLUSION: The results of this investigation support the utility of diffusion strategies for monitoring the marrow and provide further evidence of a relationship between marrow status changes and neurologic progression in HIV patients.